PENGGUNAAN APLIKASI TEMAN BIDAN PADA PENGANTIN USIA REMAJA DALAM PERENCANAAN KEHAMILAN YANG SEHAT DI WILAYAH KERJA PUSKESMAS TAMBARANGAN TAHUN 2024 - Moulina, Efani Dwi Fienty; Hapisah, Hapisah; Prihatanti , Nur Rohmah; Kirana, Rita (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Introduction: To reduce the risk of pregnancy in adolescents, education is needed so that adolescents can prepare for a better pregnancy. One way the author can do this is through an application. Website-based Teman Bidan application as a means for teenage brides-to-be to prepare for a healthy pregnancy. Objective: to determine the use of the Teman Bidan application to help teenage brides in planning a healthy pregnancy in the Tambarangan Health Center Working Area in 2024. Methods: This research uses quantitative and qualitative research methods. The type of research used is Development research or Research & Development (R&D). This research development model uses ADDIE. The population in this study were all prospective brides aged 10-19 years in the Tambarangan Health Center area with a total of 17 people from January to August 2024, the sample used was total sampling. Data collection using questionnaires with open questions and EUCS. Data were analyzed using Spearman's Rank test with a significance of α=0.05. Results: Spearman's correlation coefficient of 0.52 and p-value of 0.031 can be concluded that there is a moderate and significant positive relationship between the two variables analyzed. Conclusion: The relationship that can be obtained is a strong relationship and the relationship between these variables is in the direction of using the midwife friend application to influence teenage brides in planning a healthy pregnancy.